Spatio-temporal heterogeneity of malaria vectors in northern Zambia: implications for vector control. Issue 1 (December 2016) - Stevenson, Jennifer; Pinchoff, Jessie; Muleba, Mbanga; Lupiya, James; Chilusu, Hunter; Mwelwa, Ian; Mbewe, David; Simubali, Limonty; Jones, Christine; Chaponda, Mike; Coetzee, Maureen; Mulenga, Modest; et al.
Abstract Background Despite large reductions in malaria burden across Zambia, some regions continue to experience extremely high malaria transmission. In Nchelenge District, Luapula Province, northern Zambia, almost half the human population carries parasites. Intervention coverage has increased substantially over the past decade, but comprehensive district-wide entomological studies to guide delivery of vector control measures are lacking. This study describes the bionomics and spatio-temporal patterns of malaria vectors in Nchelenge over a two and a half year period, investigates what household factors are associated with high vector densities and determines why vector control may not have been effective in the past to better guide future control efforts. Methods Between April 2012 and September 2014, twenty-seven households from across Nchelenge District were randomly selected for monthly light trap collections of mosquitoes. Anopheline mosquitoes were identified morphologically and molecularly to species. Foraging rates were estimated and sporozoite rates were determined by circumsporozoite ELISAs to calculate annual entomological inoculation rates. Blood feeding rates and host preference were determined by PCR. Zero-inflated negative binomial models measured environmental and household factors associated with mosquito abundance at study households such as season, proximity to the lake, and use of vector control measures. Results The dominant species in Nchelenge wasAn. funestus (s.s. ) withAn. gambiae (s.s. ) as a secondary vector. Both vectors were found together in large numbers across the district and the combined EIRs of the two vectors exceeded 80 infectious bites per person per annum.An. funestus household densities increased in the dry season whilstAn. gambiae surged during the rains. Presence of insecticide treated nets (ITNs) and closed eaves in the houses were found to be associated with fewer numbers ofAn. gambiae but notAn. funestus. There was no association with indoor residual spraying (IRS). Conclusion In Nchelenge, the co-existence of two highly anthropophagic vectors, present throughout the year, is likely to be driving the high malaria transmission evident in the district. The vectors here have been shown to be highly resistant to pyrethroids used for IRS during the study. Vector control interventions in this area would have to be multifaceted and district-wide for effective control of malaria.